STUDI SIMULASI OVERSPEED TRIP (OST) PADA TURBIN UAP SHINKO 1000 KW BERBASIS FEM - Fatkur Rachmanu (Jurnal Elektra, 2019)
Many of steam turbines designs in over speed can occur. Therefore we need a device to control speed of shaft (Overspeed Trip). Speed of rotor is always maintained so as not to more rotation to hinder uncontrolled. The graph increases between the speed and time of decreasing the rotational speed. In this case, over speed trips were studied using mechanical systems. In Shinko RG64 steam turbine testing with Conversion factor, 900kW max net power turbine. Turbine rated speed 10000 rpm, trip speed multiplier 10%, trip speed 11600 rpm according to API 612: 116% rated. Acceleration turbine, initial Alpha 40.29 rpm / second. OST works following the equation of the centrifugal force where when the trip speed is exceeded the lever will move out. In the results of this simulation, the trip condition is a rotation of 11600 Rpm, for 2.11 seconds and an acceleration of 19.84 Rpm / sec. The result of displacement is 41 mm. Simulation calculations may differ from actual because conditions are affected by other components such as oil quality and condition, mechanism response between components.